Enhancing Bioactivity of Titanium-Based Materials Through Chitosan Based Coating and Calcitriol Functionalization - Doymus, Burcu; Pekozer, Gorke Gurel; Onder, Sakip (SPRINGER, 2025)
Titanium (Ti)-based materials are favored for hard tissue applications, yet their bioinertness limits their success. This study hypothesizes that functionalizing Ti materials with chitosan nano/microspheres and calcitriol (VD) will enhance their bioactivity by improving cellular activities and mineralization. To test this, chitosan particles were applied uniformly onto Ti surfaces using electrophoretic deposition (EPD) at 20 V for 3 minutes. VD was then loaded onto the coated surfaces, and the release profile of VD was monitored. Human fetal osteoblastic cells (hFOB) were cultured on the VD-loaded Ti surfaces. Cellular activities such as proliferation, Alkaline phosphatase (ALP) activity, osteogenic gene expression (runt-related transcription factor 2 (Runx2), collagen type 1 (Col I), osteocalcin ( OCn), osteopontin (OP)), and mineralization were assessed. Von Kossa staining was performed to analyze mineralization, and the expression of cell adhesion proteins (N-cadherin (NC), integrin alpha V (IaV), integrin beta 3, (Ib3)) was measured. The results showed that approximately 50% of the VD released over 50 hours. The chitosan coating increased surface roughness three-fold, and this, combined with VD release, resulted in reduced cell proliferation but increased ALP activity, suggesting enhanced differentiation. VD-functionalized Ti surfaces showed statistically significant differences in osteogenic gene expressions, particularly on rougher surfaces. Additionally, the expression of cell adhesion proteins (NC, IaV, Ib3) was upregulated on VD-containing coated surfaces. Von Kossa analysis revealed that surface roughness significantly enhanced mineralization, particularly on VD-free surfaces by day 7, while mineralization on VD-containing bare surfaces started on day 14. These findings demonstrate that VD-loaded chitosan coatings significantly enhance the biocompatibility and bioactivity of Ti-based materials, highlighting their potential for applications in bone regeneration.
Keywords: Titanium; Coating; Calcitriol; Bioactivity; Cell culture; VITAMIN-D; BONE; SURFACE; ANTIBACTERIAL; ROUGHNESS; DELIVERY; CADHERIN; SYSTEMS; GROWTH; RUNX2; Engineering